Self-compassion and suicide risk: a moderated mediation model and evidence from Chinese universities - Ge, Dandan (Frontiers in Psychology, 2023)
Introduction Suicide is a major social and public health problem in the world. It is important to identify protective and risk factors for suicide. This study aimed to investigate the relationship between self-compassion and suicide risk. Methods 1143 college students were surveyed by using Chinese Self-Compassion Scale (CSCS), Depression Anxiety Stress Scale-21 Chinese Version (DASS-21), Connor-Davidson Resilience Scale (CD-RISC), and Suicidal Behaviors Questionnaire-Revised (SBQ-R). Results Negative self-compassion had a significant positive predictive effect on college students' suicide risk; in the model of negative self-compassion affecting suicide risk, negative emotions played a mediating role and the mediating role was moderated by resilience. Specifically, compared with low resilience, students with high resilience have a weaker ability to predict suicide risk by negative emotions. Discussion Negative self-compassion is a risk factor for suicide risk, reducing negative self-compassion (self-judgment, isolation, and over-identification) and enhancing resilience has a guiding effect on suicide prevention and intervention.